MORPHOLOGICAL CHANGES IN PULMONARY VESSELS IN CORONAVIRUS INFECTION - Omonov Shokhrukh Rakhimovich (Web of Journals Publishing, 2025)
It was found that the SARS-CoV-2 pathogen is characterized by causing varying degrees of changes in the endothelium and subendothelial layers of medium-sized blood vessels (muscular arteries). In particular, intermediate foci of edema and a sharp accumulation of acidic glycosaminoglycans were detected in the endothelial and subendothelial layers of muscular arteries. In order to detect these changes using histochemical methods, Alcian blue and Van Gieson stains were used. The bodies of people who died from COVID-19 infection were autopsied within 12 hours, and during the examination, immunohistochemical examination of the lung tissue of the corpse was performed, morphological changes in the tissues were studied and analyzed. Analysis of the study results showed that a high rate of vascular endothelial cell damage was characteristic of small precapillary and capillary blood vessels.
Keywords: SARS‐CoV‐2, COVID‐19, pulmonary blood vessels, histochemical, immunohistochemical, endothelium, subendothelium, thrombus.